Кризис в Каталонии: проблемы и последствия - Alexander A. Orlov (Ибероамериканские тетради, 2017)
In the article the problems created by the crisis in Catalonia are considered. The author focuses on an unprecedented wave of the russophobia that has captured a part of the political class of Spain which destroys the basis of the Russian-Spanish relations. At the same time, as it is noted in article, Spain and its people endure today an important period of self-identiﬁcation in new conditions which can be completed successfully in case of avoiding the division of Catalans into winners and losers.